Incidence of childhood brain and other non-haematopoietic neoplasms near nuclear sites in Scotland, 1975-94. Issue 5 (1st May 1999) - Sharp, L; McKinney, P A; Black, R J
Abstract : OBJECTIVES: To examine the risk of cancers other than leukaemia and non-Hodgkin's lymphoma in children resident in the vicinity of nuclear sites in Scotland. METHODS: The study dataset comprised registrations of cancer other than leukaemia and non-Hodgkin's lymphoma diagnosed in children aged under 15 in the period 1975-94. These were validated for completeness and accuracy and analysed in two groups: (a) tumours of the central nervous system and (b) other malignant tumours (excluding leukaemia and non-Hodgkin's lymphoma). Around each nuclear site observed cases (O) were enumerated and expected numbers (E) calculated with adjustment for age, sex, deprivation, and an urban-rural category. Stone's maximum likelihood ratio test (MLR) was used to determine whether there was any evidence of increased risk of these neoplasms among children living within 25 km of one of the nuclear sites investigated. The significance level of each MLR statistic was estimated by simulation. RESULTS: More tumours of the central nervous system were observed than expected within 25 km of Dounreay (O/E = 1.14), Hunterston (1.14), and Rosyth (1.22). These results were based on 2, 26, and 136 observed cases, respectively. The unconditional MLR was significant only for Rosyth (p = 0.006). The conditional application of the MLR test for Rosyth was not significant (p = 0.771). For the group of other malignant neoplasms, the unconditional MLR test was not significant for any of the seven sites. CONCLUSIONS: There was no evidence for generally increased risk of either tumours of the central nervous system or other malignant tumours in children living near nuclear sites. The significant excess of tumours of the central nervous system around Rosyth is likely to be due to the high incidence of these tumours in east central Scotland. Further investigations in this area are warranted.